Efficacy, Effectiveness, and Efficiency - Patel, Prakash (National Journal of Community Medicine, 2021)
Efficacy, Effectiveness, and Efficiency are widely used term in health care management. Efficacy means getting things done (is it working?), effectiveness means doing the proper things (is it actually working well?), and efficiency means doing things right (is it working within the most economical way?). It’s helpful to consider them during this particular order. First, confirm the answer can actually achieve the specified result, albeit that efficacy requires very specific conditions. Then, test your solution during a real-world environment. Finally, if the answer is effective, find out ways to form it more economical more efficient. This article describes the meaning and usage of these three terminologies in context of health care setup.